(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Biometrics based authentication techniques have gained much importance in recent times. The reliability of any automatic biometric system strongly relies on the precision obtained in the grooves extraction process. A number of factors damage the correct location of the groove. Among them, poor image quality is the one with the most influence. The proposed alignment-based elastic matching algorithm is capable of finding the correspondences between grooves without resorting to exhaustive research. Lip features are extracted from the lip print of individuals using edge detection technique by studying the spatial orientations of the grooves present in the lip. The standard deviation and the variance are calculated between the segmented images and within the images. The main idea behind this approach is to identify human beings uniquely from their inherent physical qualities. Identifications using lip print biometric eradicate the problems associated with traditional methods of human identification.